2019
DOI: 10.1177/1558925019837806
|View full text |Cite
|
Sign up to set email alerts
|

Investigating electromagnetic shielding effectiveness of knitted fabrics made by barium titanate/polyester bicomponent yarn

Abstract: Electromagnetic pollution is a problem that damages all creatures and electronic devices. Most of the electronic devices we use at homes emit electromagnetic radiation. Conductive textile surfaces are used for electromagnetic shielding applications. However, to provide electromagnetic shielding, there has not been any study on the bicomponent fiber production with barium titanate. For this purpose, in this study, bicomponent yarns were produced using three different adding ratios of barium titanate. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…It was found that barium titanate affected the electromagnetic shielding properties of fabric samples. Consistent with our previous study [39], EMSE values of fabrics increased compared to the reference fabrics. The range of 20 dB ≥SE> 10 dB EMSE is classified as "good" and 10 dB SE > 7 dB EMSE is classified as "moderate" in "General Use" by The Functional Technical Textiles Standard.…”
Section: Sheet Resistance and Electromagnetic Shielding Effectivenesssupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that barium titanate affected the electromagnetic shielding properties of fabric samples. Consistent with our previous study [39], EMSE values of fabrics increased compared to the reference fabrics. The range of 20 dB ≥SE> 10 dB EMSE is classified as "good" and 10 dB SE > 7 dB EMSE is classified as "moderate" in "General Use" by The Functional Technical Textiles Standard.…”
Section: Sheet Resistance and Electromagnetic Shielding Effectivenesssupporting
confidence: 92%
“…In our previous study [39], mechanical properties and electrical conductivity properties of barium titanate/ polyester bicomponent yarns were investigated. Knitted fabrics were produced from bicomponent yarns with two different fabric densities using a circular knitting machine.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Several textile-based EMI shielding materials, incorporating various conductive elements, have been developed with either conductive fibers or non-conductive fabric substrates including polyester, polyamide, cotton, and thermoplastic polyurethane. [19][20][21][22][23][24][25] However, the majority of documented conductive fibers are composed of conductive fillers and polymer matrices. The substantial loading of conductive fillers inevitably results in a tradeoff between the textiles' mechanical stretchability/compliance and their electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Örtlek et al [24] examined the EMSE of pique, plain (E28), and double-knit structures (E18) with the shielded box shielding efficiency measurement method (30 MHz -9.93 GHz). Apart from the studies performed with the free space measurement technique [11][12][13][14][15][16][17][18][19][20] and the shielded box shielding efficiency measurement technique [21][22][23][24], there are also studies on EMSE of knitted fabrics performed with the coaxial transmission line technique [11,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Knitted fabrics give different EMSE values for each frequency when measured with different measurement techniques and / or different polarizations [11].…”
Section: Introductionmentioning
confidence: 99%